'MUSIQUE DE L'AFRIQUE' by Francois Bebey. Edition Horizons de France - 19 X 22 cm., 208 pp., 97 illustrations and four line drawings, with a 17 cm. L.P. record - Basil, Brother (International Library of African Music, 1970)
pages: 130
Keywords: African Music